2005
DOI: 10.1007/s10549-005-4170-6
|View full text |Cite
|
Sign up to set email alerts
|

RhoC-GTPase is a Novel Tissue Biomarker Associated with Biologically Aggressive Carcinomas of the Breast

Abstract: RhoC expression increases with breast cancer progression and RhoC protein level in tumor tissue is strongly associated with biologically aggressive invasive carcinomas of the breast. RhoC expression, if validated, may identify patients who are less likely benefit from doxorubicin therapy and suggests RhoC overexpression as a new target for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 31 publications
5
86
0
1
Order By: Relevance
“…This finding is consistent with a previous report suggesting that G␣12 and G␣13 expression is elevated in cell lines derived from metastatic human breast, prostate, and colon cancers (33). This up-regulation of G␣12 in intraepithelial neoplasms also is similar to what was previously reported for receptors that couple to the G12 protein (16,34) and the increased expression of the Rho proteins observed at this point or later in cancer development (16,35). Thus, it appears that the G12 signaling pathway is up-regulated as an invasion-promoting signaling unit as breast cancer progresses to an invasive phenotype.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with a previous report suggesting that G␣12 and G␣13 expression is elevated in cell lines derived from metastatic human breast, prostate, and colon cancers (33). This up-regulation of G␣12 in intraepithelial neoplasms also is similar to what was previously reported for receptors that couple to the G12 protein (16,34) and the increased expression of the Rho proteins observed at this point or later in cancer development (16,35). Thus, it appears that the G12 signaling pathway is up-regulated as an invasion-promoting signaling unit as breast cancer progresses to an invasive phenotype.…”
Section: Discussionsupporting
confidence: 93%
“…1 and Ref. 11) express relatively high levels of RHOC (24,25) indicating that RHOC can be expressed in breast carcinoma cells in the absence of miR-10b. Clearly, miR-10b has significant effects on cellular functions that underlie the progression of breast and other cancers including RhoGTPase regulation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic function of the RhoC protein has been elucidated in IBC and RhoC is consistently associated with different types of advanced cancer [17,[27][28][29][30][31][32]. Comparative microarray analysis of overexpressed-RhoC and wild-type RhoC cell lines showed that RhoC overexpression can affect the expression of more than one hundred genes that are known to be involved in various biological functions such as enhancing cell cycle progression, angiogenesis, lymphangiogenesis, and cell adhesion and invasion [33].…”
Section: Discussionmentioning
confidence: 99%